A possible TEN-T Railway Core Network in Central Europe - Lüttmerding, A.; Welitschkin, A. (Acta Technica Jaurinensis, 2011)
A main option of the review of the trans-European networks of transport is the creation of a core network as a step forward from the loosely connected 30 priority projects being its base until now. This paper presents a proposal for the Central European part of a railway core network based on various established networks and evaluation and calculation methods.